Virtual delivery of Go4Life® resources: A pilot study enhancing physical activity in older adults through pre- and post-intervention evaluation - Nazia Naz S. Khan, MD, MS; Syed S. Raza, BS; Nikhil Regmi, MD; Ling Wang, Ph.D (Archives of Gerontology and Geriatrics Plus)
The increase in life expectancy and prevalent inactivity linked to aging and concurrent health issues emphasize the need for accessible, regular motivational interventions in the era of mHealth. In this pre-post intervention study of adults aged 50 and older, we customized the high-quality, publicly available Go4Life® resources from the National Institute of Aging (NIA) to create automated motivational text messages with video clips, and periodic questionnaires. Twenty subjects received brief education on exercise benefits, along with weekly automated text messages, questionnaires, and feedback via the Dialog Health platform. Participants were followed weekly for 3 months. Primary outcomes included physical activity (PA) frequency, level, and duration pre-and post-intervention. Secondary outcomes included weekly changes in activity level developed from the NIA's Track your activity sheets and RAND 36-Item Short Form Survey Instrument (SF-36) questionnaires. The Generalized Estimating Equation with ordinal data is employed to find the average change in PA over 12 weeks. Only 13 subjects completed both the pre & post-surveys. The mean age was 61 years (age range of 50–73 years), and the mean BMI (range: 21.45–42.69) was 30.5; 55 % were females and 45 % males. Our study showed a statistically significant increase in the frequency of strengthening (mean = 1.23 (SD = 0.44) pre-intervention and mean = 2.08 (SD = 0.95) post-intervention, p = 0.02) and balancing ((mean = 1.31 (SD = 0.48) pre-intervention and mean = 2.31 (SD = 1.11) post-intervention, p = 0.02) exercises post intervention. No significant difference in responses to SF-36 questionnaires pre-and post-intervention. A larger study is warranted to determine further the effectiveness of periodic virtually delivered Go4life® resources to increase PA among older adults.